2021
DOI: 10.1155/2021/4632722
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Application of Fuzzy Decision Tree Algorithm Based on Mobile Computing in Sports Fitness Member Management

Abstract: After the reform and the opening, the economy of our country has developed rapidly, and the living conditions of the people have become better and better. As a result, they have a lot of time to pay attention to their health, which has promoted the rapid development of the sports and fitness industry in my country. In response to the increasing development of the sports and fitness sector of my country, the current state of the administration of members of the sports fitness industry does not keep pace with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Based on this, Gu Z uses the fuzzy decision tree algorithm to build a decision tree according to the characteristics of customer data and the loss of existing customers. Analysis of the situation is of strategic significance to improve the competitiveness of clubs [ 10 ]. Decision trees are one of the most popular machine learning algorithms that repeatedly divide data into groups or classes.…”
Section: Related Workmentioning
confidence: 99%
“…Based on this, Gu Z uses the fuzzy decision tree algorithm to build a decision tree according to the characteristics of customer data and the loss of existing customers. Analysis of the situation is of strategic significance to improve the competitiveness of clubs [ 10 ]. Decision trees are one of the most popular machine learning algorithms that repeatedly divide data into groups or classes.…”
Section: Related Workmentioning
confidence: 99%
“…Curran and Standage [20] put forward new ideas, as well as the overall instructional reform and experiment under its guidance, including PE teaching objectives, teaching contents, teaching methods, organizational forms, and teaching means, and gradually established one group or even several groups, in line with the spirit of reform and the teaching reality of colleges and universities in China's teaching procedures with strong operability and systematization, corresponding structure and function of PE teaching curriculum and teaching process structure, and framework or type [20]. Gu and He [21] put forward that there are still many problems in the current PE teaching in higher vocational colleges, and the teaching ideas cannot keep up with the development requirements of the times. When carrying out PE teaching, they are greatly influenced by the traditional teaching ideas, and the teaching methods are mainly classroom teaching, focusing on the teaching of knowledge points in textbooks, but there is a lack of teaching on physical skills [21].…”
Section: Related Workmentioning
confidence: 99%
“…In order to accelerate the development of the sports and fitness industry, Gu and He used ID3 fuzzy decision tree to build a tree according to the characteristics of customer data and the loss of customers, and analyzed the main factors of customer changes. Finally, it was concluded that the accuracy of ID3 fuzzy decision tree was as high as 97.8%, which could accurately analyze the causes of customer loss [13]. Li et al have designed a system based on ID3 and C4 5.…”
Section: Related Workmentioning
confidence: 99%
“…We sum each row of the normalized matrix and then calculate the eigenvector of the matrix, which is the weight vector, as shown in equation (13). In equation ( 13), the sum value of each row is as follows:…”
Section: Computational Intelligence and Neurosciencementioning
confidence: 99%